2010
DOI: 10.1007/s11010-010-0560-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cellular levels of inositol polyphosphates during apoptosis

Abstract: Accumulations of higher inositol polyphosphates, diphosphoinositol polyphosphates or pyrophosphates, have been implicated to mediate cellular apoptosis. Whether cellular levels of lower inositol phosphates (lower than inositol hexakisphosphates) change during apoptosis is not known, although these inositol phosphates are known to play crucial roles in a number of cellular signaling processes including calcium mobilization. Therefore, in this study, we have examined changes in cellular levels of inositol phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Recent studies from various laboratories including data published from our laboratory (Agarwal et al 2010;Agarwal et al 2009) have demonstrated a close association between cytosolic concentrations of InsPs and cell death induction by apoptosis. Further studies from other laboratories have shown that lower concentrations of InsP 6 promoted cell proliferation, while higher concentrations led to induction of apoptosis Helmis et al 2013).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Recent studies from various laboratories including data published from our laboratory (Agarwal et al 2010;Agarwal et al 2009) have demonstrated a close association between cytosolic concentrations of InsPs and cell death induction by apoptosis. Further studies from other laboratories have shown that lower concentrations of InsP 6 promoted cell proliferation, while higher concentrations led to induction of apoptosis Helmis et al 2013).…”
Section: Introductionmentioning
confidence: 88%
“…The [ 3 H]-InsPs in the supernatants were analyzed by anion exchange chromatography as described by Agarwal et al (2010). Briefly, clear supernatants were subjected to gravity fed columns packed with AG-1Ă—8 anion exchange resin (formate form, 100-200 mesh size, Bio-Rad Laboratories, Hercules, CA).…”
Section: Minpp1 Enzyme Assaymentioning
confidence: 99%
“…This compound has been employed in growth inhibition assays of human tumor cell lines (De Lima et al, 2015), as a protective agent in fishes with copper exposure (Jiang et al, 2014), as indicator during cellular apoptosis (Agarwal et al, 2010). Other compound: Maltose (0.02%) is a disaccharide that it has too many applications.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, inositol polyphosphates (InsPs) were shown to play signaling roles in the regulation of calcium mobilization, cell growth, vesicular transport, gene expression, and export of mRNA and apoptosis [30][31][32][33][34]. MINPP1 is an ER luminal soluble protein and dephosphorylates InsPs by removing specifically phosphate group at position 3 and association with apoptosis has been described extensively [17,[35][36][37][38][39][40][41]. MINPP1 is the only ER resident enzyme that can hydrolyze inositol pentakisphosphate and inositol hexakisphosphate and it exhibits characteristics of a stress-responsive molecule during ER stress-induced apoptosis regardless of the underlying involved mechanisms [42].…”
Section: Discussionmentioning
confidence: 99%